Real interest rates and fractional integration : the case of emerging markets - Koç, Hale. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2010., 2010)
This thesis is composed of two essays applying fractional integration analysis to (i) real interest rate series of Turkey using various de nitions (ii) real interest rate series of 19 emerging economies. Despite the existence of papers discussing fractional dynamics in real rates of U.S. and OECD countries, very little is known about this kind of dynamics in the real interest series of emerging markets. Augmented e cient fractional unit root test is implemented to conduct inference on the order of integration real rate series of Turkey and emerging markets. Possible existence of deterministics in the data is taken into account by considering two cases of the test- no trend and linear trend. As far as Turkish real rate series are concerned empirical results suggest that 2 out of the 6 real interest rate series studied are characterized by fractional unit roots. Results are observed to be responsive to maturity. On the contrary, inclusion of a linear trend doesn't alter the results. When economic causes of persistence are concerned, macroeconomic fundamentals like in ation, scal de cit, uncertainty as well as credibility and risk premium seem to play role. As far as emerging economies are concerned results suggest that for the majority of the countries studied, estimated order of integration is above 0.5, pointing out the existence of non?stationary but mean reverting dynamics in the data. Upon implementation of the test, null hypothesis of a unit root is rejected in favor of a general fractional alternative for 9 emerging countries. It is also observed that test results are responsive to inclusion/exclusion of deterministics. Presence of fractional dynamics in more than half of the countries is in line with what is previously found for developed economies.
Keywords: Interest rates -- Turkey.